Engaging with works of fiction - Wolfgang Huemer (Rivista di Estetica, 2019)
The contemporary debate in the philosophy of literature is strongly shaped by the anti-cognitivist challenge, according to which works of literary fiction (that contain propositions that are neither literally true nor affirmed by the author) cannot impart (relevant) knowledge to the readers or enrich their worldly understanding. Anti-cognitivists appreciate works of literary fiction for their aesthetic values and so risk to reduce them to mere ornaments that are entertaining, but eventually useless. Many philosophers have reacted to this challenge by pointing at ways in which works of literary fiction can be informative even though they lack worldly reference: it has been argued, for example, that fictions work like thought experiments; that they add not to our theoretical knowledge, but to our know-how or to our phenomenal knowledge; or that that they help readers to understand the perspectives of others. A stubborn defense of literary cognitivism, however, risks to collapse into an instrumental understanding of literature. In my paper I will suggest that both sides in the debate focus too narrowly on semantic features of the works in question that are tied to what I will call the “referential picture” of language. A shift of perspective is needed: for one, we ought to fully appreciate that the term “literature” does not refer to a homogeneous phenomenon, but rather to a very heterogeneous and multifarious set of works that are read by many different readers for many different reasons in many different ways. Second, we need to understand that these works have in common much more than the semantic peculiarity of lacking worldly reference: they are a unique means of communication between authors and readers – and in particular the role of the latter is often neglected in contemporary debate. These two points should help us to get a more comprehensive understanding of the practice of literature and the vast range of values we can find in works of literary fiction – and the interplay between them.